Paradigma Cashless Society Dan E-Commerce Di Indonesia, Keberhasilan Pemulihan Ekonomi Atau Euforia? - Risky Ainur Hardianti; Intan Permatasari; Ratih Nur Wahyuni (Jurnalku, 2022)
The increasing value of e-commerce transactions in Indonesia has an important role in economic recovery during Covid-19 pandemic and shows that Indonesia has a very large base of consumers. This study aims to discuss cashless payments and highlight the importance of the huge e-commerce base in Indonesia that can significantly encourage the development of cashless society. The research method used in this paper is a qualitative approach with scoping review. The results show that although the growth of e-commerce transactions is increasing, most consumers still use cash on delivery payments. In addition, the development towards a cashless society has also triggered consumptive behavior in the community, such as impulsive buying and unplanned buying. The conclusion of this paper is that the use of e-payments in e-commerce in Indonesia turns out to be partly motivated by the mere needs of pleasure and euphoria of the digital economy. Although the development of e-commerce can lead to consumerism, if used properly this can support the cashless society movement in Indonesia. Peningkatan nilai transaksi e-commerce di Indonesia berperan penting dalam pemulihan ekonomi akibat pandemi Covid-19 dan menunjukkan bahwa Indonesia memiliki basis konsumen yang sangat besar. Penelitian ini bertujuan untuk membahas fenomena penggunaan cashless payment oleh masyarakat Indonesia dan menyoroti apakah basis e-commerce di Indonesia secara signifikan dapat mendorong perkembangan cashless society. Penelitian dilakukan secara kualitatif dengan scoping review. Hasil penelitian menunjukkan bahwa sebagian besar konsumen masih memilih menggunakan metode pembayaran cash on delivery (COD) meskipun pertumbuhan transaksi e-commerce meningkat. Selain itu, perkembangan menuju cashless society juga memicu terjadinya perilaku konsumtif di masyarakat seperti impulsive buying dan unplanned buying. Simpulan dari penulisan ini adalah penggunaan e-payment pada transaksi e-commerce di Indonesia ternyata sebagian memiliki motivasi pencapaian kesenangan dan euforia ekonomi digital semata. Meskipun perkembangan e-commerce dapat menimbulkan budaya konsumerisme, tetapi jika hal ini dimanfaatkan dengan tepat maka dapat mendukung perwujudan cashless society di Indonesia.